Search 74,379 tutors
FIND TUTORS
Ask a question
0 0

simplify f(-t^2 +3) when f(x)= 4x[sqr(3-x)]

Tutors, please sign in to answer this question.

1 Answer

The question is asking you to substitute the "x" in the equation with "(-t2+3).
This gives you:
f(-t2+3)=4*(-t2+3)*√(3-(-t2+3))
Simplify by using distribution.
So,
4*(-t2+3)=-4t2+(4*3)=-4t2+12
And,
3-(-t2+3)=3+t2-3=(3-3)+t2=0+t2=t2
REMEMBER that a negative times a negative equals a positive (-1*-t2=t2)
Now you have:
f(-t2+3)=(-4t2+12)(√t2)
You know that:
(√t2)=t
So,
f(-t2+3)=(-4t2+12)t
Distribute the "t" through the parenthesis
ANSWER:
f(-t2+3)=-4t3+12t

Woodbridge precalculus tutors